Surrogacy and Legal Parenthood in Greece – One Size Fits (Almost) All - Vasileiou, Marianna (Central European Academy Law Review, 2025)
The Greek legal framework governing the application of surrogacy is strictly defined and derives from four specific laws: Nos. 3289/2002, 3305/2005, 4272/2014 and 4958/2022. In order to safeguard the assisted parent(s) as well as the surrogate and establish legal family bonds between the child and the social mother, the legislation sets out specific prerequisites, such as the inability of the social mother to carry a child, the existence of a prior judicial authorisation, a written agreement between the parties and the prohibition of using the surrogate’s eggs. However, the (excellent for the creation of legal family bonds) existing legal framework in Greece silently denies surrogacy to single men and gay or lesbian couples, reserving it only for straight couples and single women. This is a real-life issue largely ignored in everyday practice, which results in the birth of children without any legal family bond with their parent(s). The analysis of the legislation has identified three key issues on single men’s and gay or lesbian couples’ access to assisted reproduction: (1) Greek legislation remains silent on the issue; (2) Greek case-law is scant in the cases of single men and non-existent in the cases of gay or lesbian couples; (3) Greek legislation needs to be amended so that single men and gay or lesbian couples have unambiguous access to surrogacy, medical specialists can provide unhindered services to them and, most importantly, children born that way share a legal bond with their parent(s). The consensus for an overall reform of the legal framework governing single men and gay or lesbian couples to medically assisted reproduction in Greece, granting equal access to it for everybody – regardless of their sex or their sexual orientation – is absolutely imperative.